Desempenho de ouvinte e tatos-intraverbais na aquisição de relações espaciais de indivíduos com Transtorno do Espectro do Autismo - Silva, Elaine de Carvalho (Universidade Federal de São Carlos, 2021)
The general objective of the present thesis covered two questions: 1. To verify if the stimuli to the abilities of motor perception (proprioception) and of perception of spatial relations (exteroception) favor the acquisition of the repertoires of listener and tact-intraverbal responses of Autism Spectrum Disorder (ASD) children with School-age; 2. Check if the procedures and designs for stimulus control (used in empirical studies) were efficient (economy of teaching) and effective (producing new behaviors) to enable the acquisition of a language repertoire not directly taught, analyzing the functional independence or dependence relations between speaker (tact-intraverbal) and listener (follow instructions) repertoires from questions about spatial relations (front / back / right side / left side) for body parts and objects. This second question aimed to contribute to the literature that discusses which is the best teaching route to cause the emergence of an operant not directly taught (from speaker to listener or from listener to speaker). Thus, this thesis is presented in the form of a compendium of articles, being a systematic review article (Study 1) and three empirical articles (Studies 2, 3 and 4). The participants in the empirical studies were eleven children with ASD aged between six and fourteen years. Three children attended regular school and eight children attended institutions. Study 2 was a case study with an ABAB design. Study 3 involved six participants and the design used was an alternate treatment coupled to the multiple baseline design across participants. Study 4 encompassed four participants and the multiple probes design across participants was used. Based on the data obtained, the three empirical studies expand on previous findings on the proposition that teaching speaker repertoires is more effective for the emergence of listener repertoires than the other way around, in addition to corroborating the same efficacy for other operants and spatial relationships such as the intraverbal. It also expands on previous findings from studies that used spatial relations such as front / back and right / left, however, offering a concrete dimension through the use of the participant's own body parts and later generalization to new relations with objects in the environment. The data from the literature review study indicated that there was consonance between studies on a correlation between motor development and language acquisition in children with ASD; however, the authors agree that there is not enough evidence to prove this statement. Thus, they suggest that longitudinal studies be carried out to reaffirm these possibilities. Therefore, it is opportune to add the following suggestions: that educators and therapists include the teaching of motor skills when carrying out teaching planning or individualized care for students with ASD; that researchers continue the variability of procedures and designs, as well as the age of the participants and their conditions (levels of severity and comorbidities) to validate (or not) the hypothesis of the correlation between the development of the motor system and the language of children with ASD.
Listener and intra-verbal tact performance in acquiring spatial relationships of individuals with Autism Spectrum Disorder
Keywords: Educação Especial.; Transtorno do Espectro do Autismo.; Análise do comportamento aplicada.; Tato-intraverbal.; Respostas de ouvinte.; Special Education.; Autism Spectrum Disorder.; Applied behavior analysis.; Tact-intraverbal.; Listener responses.; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM